Work Is Fun, Isn’t It? Bibliometrics Of Fun Work - Mohamad Yusuf Fahreza; Theresia Wira Harjanah (Gadjah Mada International Journal of Business, 2024)
The attention and interest in fun work have exponentially increased among practitioners and academic communities. This phenomenon replaced the old-fashioned view that created a rigid climate in the office. Many employees have adopted a fun work culture to improve employer branding and employee experiences and retain their talents. Using bibliometric techniques, this study aimed to capture the trend of research in fun work and identify research streams in fun work derived from the critical topic distributions of the fun work academic literature. We performed word co-occurrence analysis, author network analysis, and publication analysis. This study identified four streams in the science of fun work: activities to make work fun, a fun work environment system, positive effects of fun work, and support for fun work. The research trend and research streams in Fun Work provided insight for researchers to find potential issues to address in future research. They revealed the interactions as well as connections among researchers in fun work.